2010
DOI: 10.1093/humrep/deq058
|View full text |Cite
|
Sign up to set email alerts
|

Intermediate sized CGG repeats are not a common cause of idiopathic premature ovarian failure

Abstract: We therefore conclude that intermediate sized FMR1 CGG repeat alleles should not be considered a high-risk factor for POF based on current evidence.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
52
3
2

Year Published

2012
2012
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 70 publications
(61 citation statements)
references
References 20 publications
4
52
3
2
Order By: Relevance
“…28 The number of women with expanded FMR1 CGG repeat numbers in this cohort among the women with overt POI was comparable to the incidence rates reported previously. 4,26 The review of all published controlled studies on the prevalence rates of expanded FMR1 CGG repeat numbers revealed that in the absence of a familial risk, the relative risk of carrying the premutation among infertile women with reduced ovarian reserve and/or POI was marginally increased 13,27 or similar 4,28,29 in all but one study. 30 The prevalence rates of CGG repeat lengths of the intermediate range were similar among infertile women with reduced ovarian reserve and/or POI in all reviewed studies.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…28 The number of women with expanded FMR1 CGG repeat numbers in this cohort among the women with overt POI was comparable to the incidence rates reported previously. 4,26 The review of all published controlled studies on the prevalence rates of expanded FMR1 CGG repeat numbers revealed that in the absence of a familial risk, the relative risk of carrying the premutation among infertile women with reduced ovarian reserve and/or POI was marginally increased 13,27 or similar 4,28,29 in all but one study. 30 The prevalence rates of CGG repeat lengths of the intermediate range were similar among infertile women with reduced ovarian reserve and/or POI in all reviewed studies.…”
Section: Discussionmentioning
confidence: 97%
“…30 The prevalence rates of CGG repeat lengths of the intermediate range were similar among infertile women with reduced ovarian reserve and/or POI in all reviewed studies. 4,[27][28][29][30] Recently, no association with FMR1 CGG repeat length with the onset of natural menopause could be demonstrated. 31 Some of the discordant conclusions given by earlier studies may be explained by the characteristics of the control groups.…”
Section: Discussionmentioning
confidence: 99%
“…Although earlier studies suggested an association between alleles in this size range and FXPOI, larger subsequent studies did not support these initial findings. 8,9 A small number of patients meeting the criteria for FXTAS with FMR1 intermediate alleles have been described, 62 although larger studies are needed to determine the significance of this finding.…”
Section: Fx 312: Intermediate (Gray Zone Inconclusive Borderline)mentioning
confidence: 99%
“…There is no evidence to support an association between high normal and intermediate range FMR1 alleles with a risk of POI. 8,9 Older males and females with premutations are at risk for FXTAS. [10][11][12][13][14][15][16] FXTAS is a late-onset, progressive development of intention tremor and ataxia often accompanied by progressive cognitive and behavioral difficulties including memory loss, anxiety, reclusive behavior, deficits of executive function, and dementia.…”
mentioning
confidence: 99%
“…Although those with this allele were previously considered to have no specific phenotype, Bretherik et al [30] found an increased intermediate carrier prevalence of 16 % among POI patients compared to 4.8-7.1 % of controls. Contradictory to this, a study by Bennett et al [31] reported that although the presence of a premutation allele was statistically significant in POI patients compared to controls, intermediate alleles were not found to be increased among POI women.…”
Section: Fragile X Mental Retardation 1 (Fmr1)mentioning
confidence: 93%